The Implementation of the 2013 Curriculum of English at SMKN 1 Bantaeng: an Evaluative Study - Ashar Ashar; Irmawati Irmawati (Universitas Negeri Makassar, 2016)
The objectives of the research were to obtain a descriptive account of (1) the lesson plans of English language learning based on the 2013 Curriculum at SMKN 1 Bantaeng, (2) learning and assessment process of English language learning based on the 2013 Curriculum at SMKN 1 Bantaeng, (3) supporting factors and obstacles that the English teachers at SMKN 1 Bantaeng face in implementing the 2013 Curriculum of English. The researcher employed descriptive qualitative method. The subjects werefour English teachers of SMKN 1 Bantaeng who participated in this research. All the subjects were selected through purposive sampling. The data of this research were collected by using triangulation technique by combining observation, interview and examining document technique. The obtained data were analyzed in four major phases namely data collecting, data reduction, data display, and conclusion. The result of the research revealed that (1) Lesson plans prepared by English teachers at SMKN 1 Bantaeng were generally well arranged. (2) a. The implementation of English learning process at SMKN 1 Bantaeng based on the 2013 Curriculum still had many shortcomings. The very prominent shortcomings were the aspect of preliminary activities, the implementation of integrated learning, the selection of sources and media, as well as on the closing activities. b. The implementation of assessment process on English learning based on the 2013 Curriculum at SMK 1Bantaengwas not done well, because most of the components of the assessment were not carried out. (3) Supporting factors on the implementation of the 2013 Curriculum of English included (a) the high commitment of the school and government, (b) the distributed guidelines, syllabus, and text book, and (c) the school facilities. Meanwhile the obstacles consisted of (a) the lacking time allocation, (b) the complicated assessment system, and (c) the lack of teachers' understanding on the 2013 Curriculum. Key words: the 2013 Curriculum, ELT plans, practices and assessments,perception.